Model dan Strategi Pengentasan Pengangguran Terdidik (Studi Kasus di Provinsi Jambi) - Siswoyo Siswoyo; Asaibani Asaibani; Ahmad Soleh (J-MAS (Jurnal Manajemen dan Sains), 2023)
Unemployment is still a major problem in almost all countries, especially educated unemployment. Educated unemployment is considered to be a fundamental problem because of the match between the level of education and the availability of employment opportunities. thus creating educated unemployment. The focus of this research is (1) analyzing the determinants of educated unemployment. (2) analyze models and strategies for overcoming educated unemployment in Jambi City. The analysis in this research uses quantitative and qualitative methods and is exploratory in nature with a Sequential exploratory Design approach. This research uses an exploratory quantitative descriptive method with a Sequential exploratory Design approach. The scope of this research was carried out in 11 provinces in Jambi Province, using secondary data. The analytical tools used in this research are multiple linear regression and qualitative SWOT analysis. The research results show that wages and inflation have a positive effect, while economic growth, labor absorption and investment have a negative effect on educated unemployment in Jambi Province. The results of the quantitative SWOT analysis show that the educated workforce in Jambi Province is in a strong condition and has opportunities and the best strategy model is a progressive strategy, a strategy to continue expanding, increasing growth to obtain maximum progress.